Analisis PPN Membangun Sendiri untuk Pengusaha Kena Pajak di Indonesia - Fany Inasius (Bina Nusantara University, 2012)
Value-Added Tax (VAT) imposition on self build activity will be distinguished if it is provided by using contractor service. As the result, different VAT treatment on both transactions above has implication to whole company‘s profit. In fact, the implementation of this regulation was ineffective because Taxable Firm will easily run away from such disadvantageous regulation. This paper focuses on comparison between VAT imposition to Taxable Firm in the form of limited liability company for self build activity and equal treatment to buildingconstruction provided by contractor. In fact, from comparative and descriptive researches, it is found that equal treatment on VAT imposition for self construction by Taxable Firm will not reduce income tax earnings compared with using contractor service. On the contrary, VAT imposition for self build activity by Taxable Firm in the form of Limited Liability Company becomes ineffective. In the other sides, because VAT in by means of selfbuild activity that can not be credited it has implication to inefficiency that in turn will not conducive to business climates.